2017
DOI: 10.1038/s41598-017-09154-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of spatial genetic variation reveals genetic divergence among populations of Primula veris associated to contrasting habitats

Abstract: Genetic divergence by environment is a process whereby selection causes the formation of gene flow barriers between populations adapting to contrasting environments and is often considered to be the onset of speciation. Nevertheless, the extent to which genetic differentiation by environment on small spatial scales can be detected by means of neutral markers is still subject to debate. Previous research on the perennial herb Primula veris has shown that plants from grassland and forest habitats showed pronounc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 88 publications
(116 reference statements)
0
1
0
Order By: Relevance
“…The study was conducted in southern Belgium, where P. veris can be found in both grassland and forest habitats (Deschepper, Brys, Fortuna, & Jacquemyn, ). Previous research (Brys & Jacquemyn, ) has shown indications of marked differences in flower morphology and associated reciprocity of sexual organs between forest and grassland populations.…”
Section: Methodsmentioning
confidence: 99%
“…The study was conducted in southern Belgium, where P. veris can be found in both grassland and forest habitats (Deschepper, Brys, Fortuna, & Jacquemyn, ). Previous research (Brys & Jacquemyn, ) has shown indications of marked differences in flower morphology and associated reciprocity of sexual organs between forest and grassland populations.…”
Section: Methodsmentioning
confidence: 99%